2021
DOI: 10.1111/codi.15804
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic port placement in robotic colorectal surgery

Abstract: Aim The aim of the study was to determine how spacing between ports and alignment of ports (oblique or vertical) influences manipulation angles in robotic colorectal surgery. Method Abdominal CT scans of 10 consecutive robotic right hemicolectomy and 10 consecutive robotic high anterior resection patients were analysed. The manipulation angles were calculated using fixed points on the preoperative abdominal coronal CT scan. Port placements were marked on the CT scan. The fixed points used to measure the manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, spacing between ports may be restricted by the size of the patient’s abdominal cavity. We have previously shown that optimal port placement for RCS can improve ergonomics for the operating surgeon [ 10 ]. For the console surgeon, port spacing distance, obliqueness of the alignment and use of different active ports can influence manipulation angles.…”
Section: Discussionmentioning
confidence: 99%
“…However, spacing between ports may be restricted by the size of the patient’s abdominal cavity. We have previously shown that optimal port placement for RCS can improve ergonomics for the operating surgeon [ 10 ]. For the console surgeon, port spacing distance, obliqueness of the alignment and use of different active ports can influence manipulation angles.…”
Section: Discussionmentioning
confidence: 99%